An asymmetric supercapacitor with excellent cycling performance realized by hierarchical porous NiGa2O4 nanosheets. Issue 36 (29th August 2017) - Liu, Shude; Hui, Kwan San; Hui, Kwun Nam; Li, Hai-Feng; Ng, Kar Wei; Xu, Jincheng; Tang, Zikang; Jun, Seong Chan
Abstract : Cycling stability of an asymmetric supercapacitor is enhanced using hierarchical porous NiGa2 O4 nanosheets as cathode electrode. Abstract : Rational design of the composition and electrochemically favorable structural configuration of electrode materials are highly required to develop high-performance supercapacitors. Here, we report our findings on the design of interconnected NiGa2 O4 nanosheets as advanced cathode electrodes for supercapacitors. Rietveld refinement analysis demonstrates that the incorporation of Ga into NiO leads to a larger cubic lattice parameter that promotes faster charge-transfer kinetics, enabling significantly improved electrochemical performance. The NiGa2 O4 electrode delivers a specific capacitance of 1508 F g −1 at a current density of 1 A g −1 with a capacitance retention of 63.7% at 20 A g −1, together with excellent cycling stability after 10 000 charge–discharge cycles (capacitance retention of 102.4%). An asymmetric supercapacitor device was assembled by using NiGa2 O4 and Fe2 O3 as cathode and anode electrodes, respectively. The ASC delivers a high energy density of 45.2 W h kg −1 at a power density of 1600 W kg −1 with exceptional cycling stability (94.3% cell capacitance retention after 10 000 cycles). These results suggest that NiGa2 O4 can serve as a new class cathode material for advanced electrochemical energy storage applications.